Influence of temperature on sorption process in hemp concrete. (1st March 2016) - Aït Oumeziane, Yacine; Moissette, Sophie; Bart, Marjorie; Lanos, Christophe
Highlights: Hemp concrete sorption isotherms are measured at two different temperatures. Both coupled hysteresis and temperature effects are investigated. Hysteresis and thermodynamic models are used. Abstract: Hemp concrete is a bio-based material which is currently undergoing a growing development. Its hygrothermal behaviour highly depends on the evolution of the moisture content which has a significant influence on heat and moisture transfer. Hysteresis phenomenon and temperature effects on sorption process make difficult the prediction of the moisture content evolution. Hysteresis phenomenon determines the equilibrium moisture content during successive adsorption/desorption cycles. Temperature influences also the equilibrium moisture content: the warmer the temperature, the lower will be the equilibrium moisture content at the same relative humidity. These two phenomena are most often neglected for modelling the moisture content evolution in heat and moisture transfer models. This can cause significant discrepancies to predict the hygrothermal response of a material subjected to climatic variations. This paper intents to contribute to the better knowledge of such sorption processes by providing new measurements and by analysing and comparing different theoretical approaches. Some adsorption and desorption main and intermediate scanning curves are measured at two different temperatures. Models taking into account these phenomena are presented. The comparison between experimental and numerical results shows that the theoretical approaches investigated are promising.